Photographic estimation of wild boar damage to alpine grazing pastures in the Carpathian Mountains of central Romania - Engeman, Richard; Cattaruzza, Renate; Cattaruzza, Marco; Fischer, Justin (Environmental science and pollution research, 2016)
Observations of wild boar damage to alpine grazing pastures in Romania’s Carpathian Mountains were collected using photographs of the slopes from vantage points. We mapped the rooted areas and then used GIS software to estimate the relative proportions of the total grazing areas visible in the photographs that were damaged by wild boar. The amounts of damage from our two demonstration pastures were 11.2 and 13.5 %. Pastures are rented for summer grazing with grazing density monitored. Wild boar damage essentially decreases the economic benefit received for the cost of the grazing rights. This paper appears to be the first documentation of the very direct costs to livestock owners from significant wild boar rooting within rented pastures. The photographic method we present provides a quick and efficient means to quantify damage to alpine grazing pastures and may have broad application for mountainous areas where swine damage (or other disturbance) occurs and there is sufficient visibility of the damaged habitat.
Gesehen am 07.05.2020